Prevalence and Costs of Five Chronic Conditions in Children. (October 2016) - Miller, Gabrielle F.; Coffield, Edward; Leroy, Zanie; Wallin, Robin
The objective is to examine the prevalence and health-care costs associated with asthma, epilepsy, hypertension, food allergies, and diabetes in children aged 0–18 years. Prevalence was calculated using 2005–2012 Medical Expenditure Panel Survey (MEPS) data, a population-based, nationally representative sample. Using MEPS, two-part models estimated the cost of each condition for all children while controlling for sociodemographic categories. Prevalence rates varied by race and ethnicity across conditions. Females had higher prevalence of all chronic conditions, except epilepsy. An additional US$1, 377.60–US$9, 059.49 annually were spent on medical expenses for children aged 0–18 years, with asthma, diabetes, or epilepsy compared to children without these conditions. This is the first study to examine the costs and prevalence of chronic health conditions in children and adolescents using a single data set. Understanding the odds of having a condition by sociodemographic categories highlights disparities that can potentially inform school nurses on the best allocation of resources to serve students.